Wet heat treatment of Nagpur mandarin (Citrus reticulata) fruits to reduce decay loss - KUMAR, DINESH; RAM, LALLAN; KUMAR, SUNIL; KHADSE, ARCHANA (The Indian Journal of Agricultural Sciences, 2018)
The study was conducted to determine the effects of hot water, temperature, duration of submergence under different storage conditions. Nagpur mandarin (Citrus reticulata Blanco) fruits subjected to wet heat treatments, viz. 600C for 30 and 60 seconds, 550C for 60 and 90 seconds, 500C for 90 and 120 seconds, 450C for 120 and 150 seconds and control. The observations were recorded for 21 days under ambient condition and 60 days under refrigerated condition. Physico-chemical and sensory attributes revealed that with low physiological loss in weight (10.41%) with high TSS (11.30%), juice recovery (47.51%) with lower deformation (10.2 mm) and Vitamin ‘C’ content (36.33 mg/100 ml) with fruits treated at 500C ±1.5 min. The microbial load of bacteria (1.07 log CFU/ml) as well as yeast and mold count (0.69 log CFU/ml) was found lower with high temperature (50˚C) and short duration (90 sec). Scanning Electron Microscope (SEM) image revealed the occurrence of melting and redistribution of natural epicuticular wax on the fruit surface, plugging with cracks and stomata which could have served as potential pathogen invasion sites.